Intercultural interactions among different roles: a case study of an international volunteer tourism project in Shaanxi, China. Issue 5 (15th April 2016) - Chen, Li-Ju
Abstract : A qualitative case study approach was used to explore the phenomenon of intercultural interactions among different roles in the Earthwatch Institute's 'Chinese Village Traditions' project, conducted in Shaanxi, China, in 2008. On-site observation, in-depth interviews, and related documentation were utilized to explore guest–host relations. The study investigated the perceptions and experiences of the 4 principal investigators, 4 student helpers, 10 international volunteer tourists, 5 domestic volunteer tourists, and 3 members of the host family. The results showed some linkages among the expectations, motivations, and intercultural interaction experiences of the different roles. The findings provide a first look at the intercultural interactions among different roles within an international volunteer tourist project in China, offering an insight into a neglected field.